Law of one price: BigMac versus Fortnite - A note - Christian Pierdzioch; Timo Schöber; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2021)
We analyze the law of one price (LoP) based on BigMac and Fortnite prices. We find a positive but less than perfect correlation between the over-/undervaluations of the two indices. While we cannot reject the LoP for the Fortnite data, we find that it does not hold for the BigMac data.
Keywords: F30; F31; 330; Fortnite; BigMac; law of one price